The Onset of Normal Field Instability in a Ferrofluid in a Reduced Gravity Environment - Krull, Brendan; Rundle, Tessa; LeCaptain, Kevin; Barhite, Justin; Gear, Amelia (Proceedings of the Wisconsin Space Conference, 2015)
A ferrofluid is a magnetic liquid comprised of nanoscale ferrous particles suspended in a low-viscosity carrier fluid. When subjected to a magnetic field, the surface of a ferrofluid deforms into peaks and valleys along the magnetic field lines. The onset of surface deformation is called the normal field instability. The theory describing the NFI identifies a critical magnetic field below which no magnetically driven surface deformations occur. The critical field depends on the gravitational acceleration and, according to the theory, should disappear as local gravitational acceleration approaches zero. While there have been previous demonstrations of the normal field instability in a reduced gravity environment, data has been inconclusive on the existence of a critical magnetic field in reduced gravity. For our work, we designed a sounding rocket payload for a suborbital rocket mission. Our experiment incorporates a ferrofluid sample and a uniform magnetic field which can be varied across a discrete range of values to observe surface deformations at different applied fields. During the microgravity portion of the rocket’s flight, we obtain video of the ferrofluid’s behavior and compare it to data taken in Earth’s gravity. A team of five undergraduate students designed and built the payload that will characterize the role of gravity in setting the critical magnetic field strength for the onset of the NFI. Data will be used to further understanding of ferrofluid behavior in a microgravity environment to advance its use in various space-based applications.